2012
DOI: 10.1108/14626001211250153
|View full text |Cite
|
Sign up to set email alerts
|

Student intentions to become self‐employed: the Ukrainian context

Abstract: Purpose -This paper aims to explore whether an integrated conceptual model (ICM) relating to factors drawn from entrepreneurial event theory (EET) (i.e. perceived desirability and perceived feasibility) and the theory of planned behaviour (TPB) (i.e. attitudes toward the behaviour, subjective norm and perceived behavioural control) explains more of the variance relating to the intention to become an entrepreneur than individual EET or TPB models. Design/methodology/approach -Survey information from 192 student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
149
5
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(186 citation statements)
references
References 24 publications
19
149
5
13
Order By: Relevance
“…Based on empirical research, scholars in Spain [27] [29], Ukraine [30], USA and Turkey [31], China [28] as well as Malaysia [33] establish that the higher the perceived behavioural control in relation to new venture creation, the higher the level of the business start-up intention.…”
Section: Perceived Behavioural Control and Entrepreneurial Intentionmentioning
confidence: 99%
“…Based on empirical research, scholars in Spain [27] [29], Ukraine [30], USA and Turkey [31], China [28] as well as Malaysia [33] establish that the higher the perceived behavioural control in relation to new venture creation, the higher the level of the business start-up intention.…”
Section: Perceived Behavioural Control and Entrepreneurial Intentionmentioning
confidence: 99%
“…members of the family, close friends, and other important people, such as teachers, successful entrepreneurs, business consultants, etc.) about whether a person will choose to follow a career as an entrepreneur seems to affect the formation of entrepreneurial intention (Ajzen, 2001;Solesvik et al, 2012;Liñán and Chen, 2006). Perceived behavioral control relects the extent to which an individual controls beliefs about the activity being studied (Solesvik et al, 2012), i.e.…”
Section: Theory Of Planned Behavior and Entrepreneurial Intentionsmentioning
confidence: 99%
“…The interplay between the components of TPB and entrepreneurial intention has attracted a considerable amount of research (Kolvereid, 1996;Tkachev and Kolvereid, 1999;Solesvik et al, 2012;Souitaris et al, 2007) but the indings are yet inconclusive. A few researchers have found a direct and signiicant relationship between the three indicators of TPB and entrepreneurial intention (Kolvereid, 1996;Tkachev and Kolvereid, 1999;Souitaris et al, 2007).…”
Section: Theory Of Planned Behavior and Entrepreneurial Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of planned behavior incorporates three elements: an individual's attitude towards specific behavior (attitude), an individual's perception of expectations (opinions) of other persons towards the selected behavior (subjective norm) and an individual's personal beliefs about their own control over the planned behavior (perceived behavioral control). A high correlation between the TPB and intentions for self-employment was reported by Solesvik et al (2012) and Liñán and Chen (2009), who, by modelling structural equations, have shown that TPB explains 55% of the variance of intentions for self-employment. On a sample of 143 Norwegian students, Kolvereid (1996b) has demonstrated that attitudes, subjective norm and perceived behavioral control affect the intentions for self-employment, while demographic characteristics of the respondents (gender, self-employed parents, experience in self-employment) affect them only indirectly.…”
Section: Previous Researchmentioning
confidence: 87%